Called & Empowered : Global Mission in Pentecostal perspective - .; Dempster, Murray A.; Klaus, Byron D. (Peabody, Massachusetts: Hendrickson Publishers, 1991)
Includes bibliographical references and index.
Includes index
Keywords: Pentecostal Churches -- Missions